Brothers Grimm or brothers Karamazov: The myth and the reality of how Russians and Ukrainians view the other - Onuch, O (E-International Relations, 2015)
Since the fall of the Soviet Union in 1991, Ukrainians and Russians have been living peacefully in two separate and independent states for nearly a quarter of a century. Much has been said about the cultural and historical links between these two ‘brotherly’ countries, but also about the tensions between the two countries’ different perspectives on nation building and democratisation processes (Jakubanecs, Supphellen, and thorbjørnsen, 2005; Janmaat, 2000; laba, 1996; Prizel, 1998; Puglisi, 2003; Shulman, 1998; Szporluk, 2000; Velychenko, 1992). Although Russian leaders, in the manner of an older brother, have consistently labelled Ukraine as the central element of Russia’s ‘near abroad’ (cameron and orenstein, 2012; Rywkin, 2003; trenin, 2006), the citizens and their foreign policies preferences have historically (i.e. on gas, on the Georgian War, on the EU and nAto) converged and diverged several times over the course of the last twenty-plus years. Yet, even though there were sensitive moments during the last twenty-plus years of Ukraine-Russia relations (october 1996 crisis, 2004 orange Revolution, gas crisis of January 2006, gas crisis of January 2009), the events of 2014 (the Euromaidan Protests, the annexation of Crimea, and the ongoing conflict in the Donbas3) are predicted by social scientists to not only sour formal relations between the two states, but also between ‘ordinary’ citizens. While there are many ‘myths’ about the way brother Russians and Ukrainians view the ‘other’ state and its people, the reality is much more complex, permeating with conflict, competition, and ideological disagreements, as in any other family. in such critical times, we must stop and ask: do Russians and Ukrainians view the events of the last year differently? or are there points of convergence? do these events affect the way Russians see Ukraine and Ukrainians see Russia? if so, how? And can we identify any shifts in views overtime from before the 2014 crisis to today? Data on the topic is difficult to find and even more difficult to assess. This is specifically the case when so many contextual variables are in flux and when little, if any, of the available data consists of either a repeated and duplicated schedule of questions, or a panel (following citizens and their views) tracking preferences over time. Thus, we must scour a variety of polls conducted at different times, by different institutions, to map out the views of Ukrainians and Russians.